Disentangling Multispecies Landscapes in Arunachal Pradesh: Religion, Ecology, Ethics - Swargajyoti Gohain (Religions, 2025)
This article considers the dilemma between advocating for a religion-based environmentalism in the Himalayas and recognising that the different cultural traditions in the region make a uniform religious environmentalism difficult to uphold. Conservationists often attempt to mobilise local communities for environmental protection by building on their religious and cultural beliefs. Yet, such forms of mobilisation tend to homogenise plural traditions by forcing them within a single fold. What is the way out of this dilemma? I offer some reflections, drawing on my empirical work in the Buddhist Himalayas, and focusing on the case studies of the yak and the black-necked crane respectively, two species which hold a special significance in Arunachal Pradesh, India. Examining these multispecies relations in Arunachal Pradesh reveal not only Buddhist values at work, but plural and evolving entanglements. The question, then, is not to see if the value is religious but if the value is more-than-human in its orientation, taking into account the entangled lives of human and non-human habitations. My broad argument is that an ethics of the environment need neither to be removed from religious ethics, nor enclosed by it. Rather than force environmental thought and behaviour into silos of particular religious traditions or conservation science paradigms, how can one see these as the function of plural habitations?